Immigration to Finland as an underaged ice hockey player : experiencing the first steps of an athletic career in a foreign country - Pohjoisvirta, Johanna (2023)
An increasing number of foreign junior ice hockey players move to Finland every year to pursue their athletic career in a competitive environment. According to the players’ views, Finland offers better opportunities to develop during junior years than their home country, and makes it is possible to play ice hockey as a professional. The dream of becoming a professional athlete is pursued by many, but only a few make it to the top.